The Study of Nursing Personnel, s Workload Caused by Patient Transferring - Abdollah Mousavi Ouri; Naser Sedghi Goyaghaj; Zahra Monjamed; Abolfazl Alamdarloo (Majallah-i Bālīnī-i Parastārī va Māmāyī, 2016)
Background and aims: One of the nursing staff’s responsibilities is patient transferring. The disproportionate burden imposed on the person according to his ability is the most important causes of occupational accidents and injuries. This study was aimed to evaluate nurseschr('39') workload caused by patient transferring in khatam ol anbiya hospital (s) in Tehran.